Promoting Financial Education to Reduce Societal Impact of Natural Hazards and Climate Change - Villalba-Romero, Felix; Liyanage, Champika; Callejón-Gil, Ángela (My University, 2023)
The scale of the losses associated with natural hazards and climate change impact is increasing during last decades. Whilst some natural hazards, as an earthquake or a tsunami produce sudden economic and human losses, other events related to climate change, such as long-period draughts, generate continuous losses, increasingly hard to recover. Undoubtedly, the recovery process of a society is directly linked to its wealth but also depends on the preparedness and capacity building in disaster resilience. Financial education plays an important role in the recovery process but often has been omitted by authors. Using existing financial instruments such as insurance products and microfinance mechanisms by most impacted SME and collectives, largely increases the community resilience and adaptation capacity. Hence, it is necessary to promote the use and development of these instruments into the local financial markets through educational actions. Through literature review process and policy analysis this research explores alternatives to promote disaster recovery and inclusive growth strategies based on financial education. The research presents a theoretical framework that includes educational actions and target groups and offers policy makers a tool to accelerate the reconstruction and transformation process derived from climate change and hazards. Discussions and results show and reaffirm how financial education should be included in climate change policies. Further research using case studies will validate and enhance the results.
Keywords: Cambios climáticos - Aspectos económicos; Pequeñas y medianas empresas; Financial instruments; Disaster recovery; Climate change; Small and Medium sized Enterprise (SME); Microfinance